Changes on Content, Structure and Surface Distribution of Lignin in Jute Fibers After Laccase Treatment. Issue 3 (4th May 2018) - Dong, Aixue; Fan, Xuerong; Wang, Qiang; Yu, Yuanyuan; Wang, Ping; Yuan, Jiugang; Cavaco-Paulo, Artur
ABSTRACT: Effect of laccase treatment on the content, structure, and surface distribution of lignin in jute fibers were fundamentally investigated. Four percent lignin was removed from jute fibers via the laccase treatment. The residual lignin in the laccase-treated jute fibers showed increased molecular weights, which indicated polymerization between lignins on jute fibers. Meanwhile, the phenolic hydroxyl content in lignin decreased during the laccase oxidation accompanied by demethylation of methoxyl groups and generation of carbonyl groups. Due to the degradation and subsequent polymerization of lignin by laccase, the bulgy lignins on jute fiber surfaces were redistributed, which made the surface neat and glossy.